Isolation and partial characterization of bacteria (Pseudoalteromonas sp.) with potential antibacterial activity from a marine costal environment from New Caledonia. (17th October 2013) - Dufourcq, R.; Chalkiadakis, E.; Fauchon, M.; Deslandes, E.; Kerjean, V.; Chanteau, S.; Petit, E.; Guezennec, J.; Dupont‐Rouzeyrol, M.
Abstract Marine bacteria are a rich source of bioactive metabolites. However, the microbial diversity of marine ecosystem still needs to be explored. The aim of this study was to isolate and characterize bacteria with antimicrobial activities from various marine coastal environment of New Caledonia. We obtained 493 marine isolates from various environments and samples of which 63 (12·8%) presented an antibacterial activity against a panel of reference pathogenic strains (Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Enterococcus faecalis). Ten out of the most promising strains were cultured, fractionated and screened for antibacterial activity. Four of them (NC282, NC412, NC272 and NC120) showed at least an activity against reference and multidrug‐resistant pathogenic strains and were found to belong to the genus Pseudoalteromonas, according to the 16S phylogenetic analysis. The NC282 strain does not belong to any described Pseudoalteromonas species and might be of interest for further chemical and biological characterization. These findings suggest that the identified strains may contribute to the discovery for new sources of antimicrobial substances to develop new therapies to treat infections caused by multidrug‐resistant bacteria. Significance and Impact of the Study With the constant increasing of bacterial resistance against known antibiotics in worldwide public health, it is now necessary to find new sources of antimicrobials. Marine bacteria from New Caledonia were isolated, tested for antibacterial activity and characterized to find new active molecules against multidrug‐resistant bacteria. This study illustrates the diversity of the marine ecosystem with potent new bacteria species. Also the potential of marine bacteria as a rich source of bioactive molecule, for example antibiotics, is highlighted.